Creating a Centre for University Faculty Learning and Teaching: Adult Education in the Academy of the Second Millennium - Marilyn E. Laiken (Adult Education Research Conference, 2000)
Although numerous attempts have been made to establish a centre for excellence in teaching and learning at the University of Toronto, none have been sustained. The author suggests that a more systemically-focused approach which uses wide consultation and collaborative planning with key stakeholders may help achieve the goal.